THE EFFECT OF MANAGEMENT AND WORKING CAPITAL POLICIES ON THE PROFITABILITY OF MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Bobby Cornelius; Sapto Jumono (Universitas Mercu Buana Yogyakarta, 2021)
The purpose of this study was to determine the effect of the receivable period, the debt period, cash turnover, investment policies, and financing policies on profitability. This study used linear regression analysis with 30 manufacturing sector companies listed on the Indonesia Stock Exchange in 2015-2017 used as a sample. The results showed that there was a statistical significance between profitability, measured through the receivable period, the working capital investment policy, and the working capital financing policy. Extension of the credit period to customers is a cost for the company. Following a conservative investment policy by having high-level short-term investments has a negative effect on profitability and firm value. While working capital financing policies have a significant positive effect on profitability, following a conservative financing policy by using more long-term debt to fund the company's operating activities has a positive effect on company profitability.